Fish swarm intelligent algorithm for bound constrained global optimization - Fernandes, Edite Manuela da G. P. (2009)
The algorithm herein presented is a modified version of the artificial fish swarm algorithm for global optimization. The new ideas are focused on a set of movements, closely related to the random, the searching and the leaping fish behaviors. An extension to bound constrained problems is also presented. To assess the performance of the new fish swarm intelligent algorithm, a set of seven benchmark problems is used. A sensitivity analysis concerning some of the user defined parameters is presented.